PO25 | Baseline thrombin generation test does not predict thrombotic events in acute leukemia: a monocentric prospective study (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Thromboembolic events and bleeding are frequent and clinically significant complications in patients with acute leukemia (AL), contributing to morbidity and mortality. Conventional coagulation assays (CCAs) and platelet count offer limited predictive value. Global coagulation assays such as thrombin generation assay (TGA) may provide a more comprehensive picture of the hemostatic state. This prospective monocentric study aimed to assess whether baseline TGA parameters could predict thrombotic events in patients with newly diagnosed AL.